2012
DOI: 10.1590/s1807-55092012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Reprodutibilidade da curva força-tempo do estilo "Crawl" em protocolo de curta duração

Abstract: O objetivo deste estudo foi analisar a reprodutibilidade dos parâmetros biomecânicos da curva força-tempo do estilo "Crawl" em um protocolo de 10 s no nado atado. Dezesseis nadadores do sexo masculino (idade: 20,4 ± 4,0 anos; tempo na prova de 100 m livre: 53,68 ± 0,99 s) realizaram dois esforços máximos de 10 s no nado atado. Os parâmetros força pico, força média, taxa de desenvolvimento de força, impulso, duração da braçada, tempo para atingir a força pico e força mínima foram representados pela média de oit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
(6 reference statements)
1
6
0
2
Order By: Relevance
“…Furthermore, the accuracy of measures assessed by standard error 18 was also better for mean forces than for maximum forces ( Table 1). These findings partially corroborate the previously established hypothesis, since the maximum force, in addition to the other kinetic variables reached by competitive swimmers in the crawl stroke presents repeatability 11 . On the other hand, it is important to note that, to the best of the authors' knowledge, the present study was the first to investigate the repeatability of tethered swimming tests for leg kicking and arm stroke in crawl swimming.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the accuracy of measures assessed by standard error 18 was also better for mean forces than for maximum forces ( Table 1). These findings partially corroborate the previously established hypothesis, since the maximum force, in addition to the other kinetic variables reached by competitive swimmers in the crawl stroke presents repeatability 11 . On the other hand, it is important to note that, to the best of the authors' knowledge, the present study was the first to investigate the repeatability of tethered swimming tests for leg kicking and arm stroke in crawl swimming.…”
Section: Discussionsupporting
confidence: 91%
“…The tethered swimming test has been used by coaches and researchers to evaluate swimmers 3,5,6 , since, considering crawl stroke, the test presents some similarities with non-tethered (free) swim for stroke rate and for some physiological responses such as blood lactate concentration, heart rate and subjective perception of effort 6,8,9 . In addition, several studies have identified an association between the outcome of the tethered swimming test and sports performance 3,10 and have verified the test repeatability for competitive swimmers 7,8,11 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, the aim of this study was to identify, through the biomechanical parameters extracted from the force-time curve of tethered swimming, the latent dimensions that would contribute most to the generation of impulse in fully tethered swimming. 21 who considered the minimum indices adopted by the entities responsible for participation in the Senior category 100m freestyle race at international, national and state level during the year in which the research was carried out; in this case, indices established in the year 2016. Swimmers achieved times of 53.12 ± 2.36s and were ranked at national level.…”
Section: Introductionmentioning
confidence: 99%
“…A literatura apresenta, basicamente, dois métodos válidos de mensuração da força aplicada durante o nado: o método de nado atado ("tethered swimming") (BARBOSA, 2010; BARBOSA; ANDRADE; MOREIRA; SERRÃO; ANDRIES JÚNIOR, 2012;DOPSAJ et al, 2002;FOMITCHENKO, 1999;KESKINEN;KOMI, 1993;MARINHO;GOMES, 1999; PAPOTI; ZAGATTO; FREITAS JÚNIOR; CUNHA;…”
Section: Introductionunclassified